Attitudes towards suicidal behavior among nursing students - Albuquerque, Roberto Nascimento de; Araújo, Elisa Marina Silva; Moreira, Tatiana Bernardes (Acta Scientiarum. Health Sciences, 2022)
The existence of an association between negative attitudes from health professionals, such as prejudice, stigma and discrimination, can lead to difficulties in dealing with a person who has attempted suicide and, consequently, to a decrease in the quality of the care provided. In this context, this article aimed to verify attitudes related to suicidal behavior among nursing students at a private educational institution in the Federal District, Brazil. It was a quantitative, descriptive study that used two questionnaires: a sociodemographic and academic one, and another with questions addressing attitudes towards suicide, called Questionnaire on Attitudes Towards Suicidal Behavior. A total of 253 nursing students participated; in general, the data revealed that they did not have any negative attitude towards suicidal people. The main attitudes that brought some difficulty to students were related to: asking about suicidal behavior and inducing someone to go ahead with it; feeling helpless when faced with a person who thinks about killing themself; lack of professional preparation to deal with patients who have gone through this psychological suffering of attempting self-extermination; and the presence of a conservative and religious attitude towards suicide. Understanding the attitudes of students in the health field, especially nursing students, still in the training period, can bring about a change in the understanding of suicidal behavior, a prejudice-free nursing care, strengthen broad discussions around the topic, openly and without taboos, as well as provide a comprehensive and humanized care.